Statistical Magnitude Analysis and Distance Determination of the Nearby F8V Stars - Dwidar, H. R.; Sharaf, A. (Engineering, Technology & Applied Science Research, 2014)
The present paper is of three folds. First, to provide some basic descriptive statistics parameters for the apparent and absolute magnitudes of the nearby stars of spectral type F8V stars. Second, to establish the frequency functions and of the absolute and apparent magnitudes for these stars. Third, to compute the distance r of these stars as a system assuming that they scatter around a mean absolute magnitude in a Gaussian distribution. The accuracy of the numerical results is satisfactory thus, the percentage error between r and the mean value is less than 0 .7%.